Education in early 2nd millennium BC Babylonia : the Sumerian epistolary miscellany - Kleinerman, Alexandra. (Cuneiform Monographs, 2011)
This book examines a collection of twenty-two literary letters and related compositions - the Sumerian Epistolary Miscellany (SEpM) - studied as part of the Old Babylonian Sumerian scribal curriculum, in an attempt to better understand the education system at this time. The author includes discussion of the nature of the letters as scribal inventions, the pedagogical function of literary letters and compilation tablets, as well as the creation, implementation and consistency of the advanced Sumerian scribal curriculum. The volume also contains critical editions of SEpM as well as ancillary Sumerian letters studied in the Nippur schools, the majority of which were previously unpublished.